2010
DOI: 10.1007/s00520-010-0908-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of palonosetron (PAL) compared to other serotonin inhibitors (5-HT3R) in preventing chemotherapy-induced nausea and vomiting (CINV) in patients receiving moderately or highly emetogenic (MoHE) treatment: systematic review and meta-analysis

Abstract: PAL was more effective than the other 5-HT(3)R in preventing acute and delayed CINV in patients receiving MoHE treatments, regardless of the use of concomitant corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 49 publications
1
56
0
2
Order By: Relevance
“…Previous meta-analyses showed that other 5-HT 3 RAs, including ondansetron, granisetron, and ramosetron, had similar rates of adverse effects when used for the prevention of PONV, 10,38 and use of palonosetron did not result in a higher incidence of adverse effects compared with other 5-HT 3 RAs for the prevention of chemotherapy-induced nausea and vomiting. 18,19 Nevertheless, we cannot easily draw a conclusion regarding the safety profile of palonosetron because the studies in this meta-analysis did not report the incidence of all common adverse effects or any rare but severe adverse events.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous meta-analyses showed that other 5-HT 3 RAs, including ondansetron, granisetron, and ramosetron, had similar rates of adverse effects when used for the prevention of PONV, 10,38 and use of palonosetron did not result in a higher incidence of adverse effects compared with other 5-HT 3 RAs for the prevention of chemotherapy-induced nausea and vomiting. 18,19 Nevertheless, we cannot easily draw a conclusion regarding the safety profile of palonosetron because the studies in this meta-analysis did not report the incidence of all common adverse effects or any rare but severe adverse events.…”
Section: Discussionmentioning
confidence: 93%
“…Méthodes Nous avons effectué une recherche systématique dans les bases de données MEDLINE Ò , EMBASE TM , le Registre central Cochrane des essais cliniques contrô lés et Web of Science Ò pour identifier les essais randomisés contrô lés qui ont abordé la comparaison de l'efficacité antiémétique dans les 24 premières heures suivant une chirurgie, du palonosétron et de l'ondansétron administrés à titre prophylactique. Les principaux critères d'évaluation étaient le pourcentage de participants éprouvant des nausées postopératoires (NPO), des vomissements postopératoires (VPO) ou les deux, dans la période précoce (0-6 heures) ou tardive (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Postoperative nausea and vomiting (PONV), the big ''little problem'', 1 is the most common postoperative medical problem. From the perspective of both patients and healthcare providers, prophylaxis of PONV is equally as important as postoperative analgesia.…”
Section: Résuméunclassified
See 1 more Smart Citation
“…Chemotherapy-induced nausea and vomiting (CINV) is a common side effect of chemotherapy for many cancer patients (Botrel TE et al, 2011;Guo-Li Wei et al, 2013). CINV may lead to discontinuation of treatment, decrease quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…So, preventing CINV during chemotherapy is important and 5-HT3 receptor antagonists are (5-HT3-RA) widely used as antiemetics in clinical (Claudio Faria et al, 2014). But one side effect of the 5-HT3 receptor antagonists is constipation, because the 5-HT3 receptor antagonists (5-HT3-RA) prevent the gastrointestinal peristalsis, at the same time (Botrel et al, 2011;Faria et al, 2013). The 5-HT3 receptors antagonists affect GI vagal afferents to inhibit the vomiting reflex, gastric distension and delaye gastric emptying (Andrews et al, 1988;Yoshioka et al, 1990;Horn et al, 2004;Badary et al, 2006).…”
Section: Introductionmentioning
confidence: 99%